PENGARUH BRAND TRUST DAN BRAND EQUITY TERHADAP LOYALITAS KONSUMEN PADA PRODUK KOSMETIK WARDAH (Survey Konsumen Pada PT. Paragon Technology And Innovation Cabang Pekanbaru) - Suci Fauziyah; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine the influence of brand trust ( X1 ) and brand equity ( X2 ) customer loyalty ( Y ) in cosmetic products Wardah ( consumer survey on PT . Paragon technology and innovation branches pekanbaru ) . The method in this research is quantitatively using SPSS 21 program , where samples were used that consumers using cosmetic products Wardah by respondents as many as 100 people sampling technique is accidental sampling using the formula slovin . The results showed that the test results simultaneously obtained from the F count was 34.888 while the value of F table 3.090 . This means that F count> F table and significant value 0,000 < alpha of 0.05 . This means that brand trust and brand equity simultaneously significant effect on consumer loyalty to cosmetic products Wardah .Keywords : brand trust , brand equity , customer loyalty